Security and development - are they two sides of the same coin? Investigating India's two-pronged policy towards left wing extremism - Basu, Ipshita (© 2011 Taylor & Francis, 2016)
This article was published in Contemporary South Asia [ © 2011 Taylor and Francis Group] and the definite version is available at: http://doi.org/10.1080/09584935.2010.537745 The Article's website is at: http://www.tandfonline.com/doi/abs/10.1080/09584935.2010.537745